Strategi Manajemen Krisis Public Relations PT. Angkasa Pura I Bandara Internasional I Gusti Ngurah Rai Bali dalam Menghadapi Dampak Erupsi Gunung Agung 2017 - Sekarbuana, Made Widya; Alit Setyawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRACT The crisis is an unexpected occurrence and the impact of the dramatic situation in an organization or company without having any time constraints and objectives, as well as airport services management company PT Angkasa Pura I Airport International I Gusti Ngurah Rai of Bali that is experiencing a crisis due to the eruption of Mount Agung in the year 2017 which resulted in the closure of the airport operations that occurred November 27, 2017 until November 29, 2017. The impact of the presence of such matters is the buildup of passenger numbers as many as 59,000 and 443 cancellations. Public Relations Ngurah Rai play a role in the crisis situation of the company by forming a crisis management strategy are related through public relations work program. Public relations crisis management strategy which became reference in this study is based on a concept expressed by Rhenald Kasali with mempertimbangan stages of the crisis that occurred in the field of appropriate concepts Steven Fink. This study uses qualitative methods ' descriptive data collection techniques in the form of an interview and documentation study based on purposive technique. Results of the study show that there are four strategy crisis management at PT. Angkasa Pura I international airport I Gusti Ngurah Rai Bali, namely identification and analysis, program execution, and recovery strategy governing programme, contained in the four stages of crisis due to Mount Agung 2017 for the company are pre-alert, phase interference, the stage of crisis, and the recovery phase. Keywords: Crisis, Crisis management Strategy, Public Relations